Transformasi Digital dan Manajemen Strategik Rumah Sakit: Peluang dan Tantangan - Purwadhi Purwadhi; Yani Restiani Widjaja; Aryo Dwi Wicaksono; Ayu Purnama Dewi (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to conduct an in-depth exploration of the opportunities and challenges faced by hospitals in implementing digital transformation as an integral component of their management strategies. Employing a descriptive qualitative approach through a literature review, the research examines multiple strategic dimensions, including technological readiness, human resource competence, government regulations, and organizational culture. The findings reveal that digital transformation offers substantial opportunities, notably in enhancing service efficiency, enabling data-driven decision-making, and expanding patient access through advanced technologies such as telemedicine and integrated hospital information systems. These advancements have the potential to improve healthcare quality, optimize operational workflows, and strengthen the hospital’s competitive positioning in the digital era. Nevertheless, the study also identifies considerable challenges that can hinder successful implementation. These challenges include inadequate technological infrastructure, organizational resistance to change, concerns over data security and patient privacy, and financial constraints related to high implementation and maintenance costs. Such barriers highlight the need for comprehensive strategic planning and adaptive management practices. The research underscores the importance of an integrated approach that synergizes technological development, human resource capacity building, and supportive regulatory frameworks. To achieve sustainable digital transformation, hospitals must adopt collaborative strategies involving multiple stakeholders, including healthcare providers, technology developers, and policymakers. The creation of a clear and realistic hospital digitalization roadmap—guided by evidence-based decision-making and supported by adequate resources—will be critical for overcoming obstacles and maximizing benefits. Ultimately, the study provides valuable insights for hospital administrators, government agencies, and academic researchers, serving as a reference for designing relevant, practical, and forward-looking digital transformation strategies. Such strategies are essential for building a superior, adaptive, and sustainable healthcare system capable of addressing evolving patient needs and emerging challenges in the healthcare sector.